IBM Rebuilds Europe: The Curious Case of the Transnational Typewriter - Paju Petri; Haigh Thomas (Cambridge University Press, 2022)
In the decade after the Second World War IBM rebuilt its European operations as integrated, wholly owned subsidiaries of its World Trade Corporation, chartered in 1949. Long before the European common market eliminated trade barriers, IBM created its own internal networks of trade, allocating the production of different components and products between its new subsidiaries. Their exchange relationships were managed centrally to ensure that no European subsidiary was a consistent net importer. At the heart of this system were eight national electric typewriter plants, each assembling parts produced by other European countries. IBM promoted these transnational typewriters as symbols of a new and peaceful Europe and its leader, Thomas J. Watson, Sr., was an enthusiastic supporter of early European moves toward economic integration. We argue that IBM’s humble typewriter and its innovative system of distributed manufacturing laid the groundwork for its later domination of the European computer business and provided a model for the development of transnational European institutions.